Propuesta de elaboración de un manual aplicando técnicas postcosecha para una plantación agrícola de guanábana “San Antonio” del Cantón Morona Provincia de Morona Santiago - Rivadeneira Castillo, Alfredo Maximiliam (2024)
Postharvest is associated with the proper management for the preservation of various agricultural products to determine their quality and subsequent marketing or consumption. With its practical implications, this research aims to develop a postharvest technique manual for the 'San Antonio' soursop plantation in Morona Canton province of Morona Santiago. The research began with a quantitative approach, collecting numerical data from the physical-chemical analysis of the soil and soursop after harvest, before and after applying the conservation techniques. The methods used were edible coating with 0.2% carnauba wax, biofilm with 0.4% corn starch, plastic coating of Low-Density Polyethylene (LDPE), and no coating as the last method. A randomized complete block design was used within the experimental design, with weight, brix degrees, and pH as variables, and data were collected on days 2, 6, and 12. The treatments were: carnauba wax, whose composition was 10 g of carnauba wax, 20 ml of glycerin, 20 ml of ethanol, 20 ml of Polysorbate 80 and 500 ml of distilled water, corn starch, whose composition was 20 g of corn starch, 2.5 g of carboxymethylcellulose, 5 ml of glycerol and 500 ml of distilled water, plastic coating (LDPE), and fruit at harvest stage, considered as (control treatment). The results of the physic-chemical analysis were regarded as the control treatment. The results of the physical-chemical analysis for weight loss, which showed less loss, were for treatment 1, with a value of 0.67 % on day 12. Similarly, the pH variation was lower for treatment one at day 12, resulting in 3.81 pH units, complying with the range established by the Colombian Technical Standard (NTC 5208). The most advisable treatment for the brix degrees variable is the edible carnauba wax coating with an average value up to day 12 of 10.06°Brix. The results obtained from the physical- chemical analysis comply with NTC 5208. Therefore, based on these findings, the postharvest techniques manual describes the recommendations for continuous improvement on the agricultural plantation.